KONDISI SANITASI LINGKUNGAN SEKOLAH DI KECAMATAN KOTO TANGAH KOTA PADANG - Widya Meisya Hardin; Helfia Edial (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
ABSTRACT The objectives of this study were (1) to determine the level of cleanliness of human waste disposal facilities / latrines and clean water reservoirs in the school environment. (2) Knowing the availability of waste water disposal facilities in the school environment of Koto Tangah, Padang City. (3) Knowing the availability of waste disposal facilities and their management in the Koto Tangah, Padang City. The results of this study indicate that (1) sanitation of latrines / toilets and the use of clean water for schools can be categorized for the level of cleanliness in each level of education for elementary schools with a good level of cleanliness with a percentage of 71.42%. For SMP the level of cleanliness is sufficient with a percentage of 43.75% and for SMA the level of cleanliness is sufficient with a percentage of 56.25%. (2) For the availability of SPAL facilities, namely SPAL made of impermeable and closed materials that meet the requirements of 8 schools with a percentage of 72.72%. And for SPAL drains discharged into septic tanks that meet the requirements of 6 schools with a percentage of 54.54%. (3) For waste disposal facilities and their management, there are 8 schools available in every room equipped with lids with a percentage of 72.72%. And for separate trash cans between wet and dry waste, there are 9 schools with a percentage of 81.81%. And for the final waste collection point (TPA) in schools, there are 2 schools with a percentage of 18.18% from 11 schools. Because 9 schools are transported by carts / trucks, the final waste collection points (TPA).